Kinerja Perusahaan Tekstil dan Garment - Darmanto Darmanto; kun ismawati (ITB AAS INDONESIA, 2020)
ABSTRACT: Bussiness competition in the textile and garment industry is now increasingly high, need to be managed properly, especially it’s financial performance. This study aims to determine the effect of capital structure on financial performance on textile and garment companies listed on the Indonesia Stock Exchange in 2016-2018 both partially and simultaneously. Capital structure is measured by Debt to Asset Ratio (DAR) (X1), Debt to Equity Ratio (DER) (X2), and Long term Debt to Equity Ratio (LtDER)(X3). Company performance is measured by Return on Investment (ROI) (Y). This research is a quantitative case study. Secondary data obtained from the annual financial statetments. The population of the research are 21 companies. The number of samples in this study were 8 companies. The analysis technique used is multiple regression to test the effect of independent variables on the dependent variable. The results showed that partially DAR and DER variables significantly influence the ROI, while the LtDER variable has no significant effect on ROI. All three variables have a significant effect on ROI simultaneousl.